(untitled) (Bioagro, 2022)
The cultivation of avocado cv. Hass (Persea americana Miller) in Colombia has grown in recent years. Among the country’s challenges is to increase the orchards’ productivity by guaranteeing grafts plants the best agronomic, genetic, and phytosanitary parameters. This work aims to evaluate for 90 days (nursery phase) the growth and development of avocado rootstocks originated from seeds with different weight ranges. A completely randomized experimental design was carried out, with treatments consisting in four Creole avocado seed weights (40-60 g, 60-80 g, 80-100 g, and over 100 g). In general, seeds greater than 80 g had the best germination percentage (over 70 %), a greater plant height, and a greater stem diameter in each of the evaluated periods. The seeds greater than 100 g presented the emergence of multiple stems at 30 days after transplanting; this fact was related to the size and reserves of the seed. The highest accumulated dry matter in stems, leaves, and total plant (without seeds) (cotyledons) were present in treatments with seeds above 80 g. These plants showed higher germination, significant more accumulation of biomass and greater vigor, which could shorten the nursery time while guaranteeing the quality of the material influenced by improved growth and seedling survival.